Korelasi Ayat Manfaat dan Mudharat Dalam Al-Qur'an: (Kajian Taqdim wa Ta’khir Perspektif Maudhu’i Dalam Tafsir Al-Misbah) - Nigita Ariyani; Nur Rokhim (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to examine the terminology of naf'an and dharran in the Qur'an. Besides this study aims to trace and analyze the meaning and correlation of the word naf'an and dharran contained in one verse. Showing the problem of how the meaning of naf'an and dharran in the Qur'an, and how the correlation of the two words in one verse, using thematic interpretation method (maudhui). This method collects verses in one theme, focused on the words naf'an and dharran. Produce naf'an which have the meaning of benefits or benefits, while dharran has the meaning of harm or damage. The first verse of the correlation between Naf'an and Dharran is because of the intention to be conveyed. The purpose includes the dimensions of unity and the dimension of warning (Indzar), the verse which discusses the dimensions of unity, among others; QS al-Maidah verse 76, QS ar-Ra'du verse 16, QS Thaha verse 89, QS al-Furqan verse 3, actually only Allah has the ability to provide benefits and harm to humans, while the statues are made as worship does not have any ability for himself. The verses that discuss the warning dimension of QS al-A'raf verse 188, Surah Yunus verse 49, QS Saba verse 42, and QS al-Fath verse 11. The existence of the punishment of hell and torment will be accepted for servants who reject Allah. The second correlation of benefit verses (naf'an) and mudharat (dharran) is the adjustment of the word for purpose taqdim's or finally what is called mura'atul isytiqaq lafazh (maintaining the harmony of the origin of the word). These verses are QS al-Maidah verse 76, QS al-A'raf verse 188, QS Yunus verse 49, QS ar-Ra'du verse 16, QS Thaha 89, QS al-Furqan verse 3, QS Saba verse 42 , and QS al-Fath verse 11 in the verse has followed the rules of taqdim and the end of the word naf'an and dharran in one verse. The word naf'an takes precedence 3 times, namely in Surah al-A'raf verse 188, QS ar-Ra'du verse 16, and QS Saba verse 42. Whereas the word dharran takes precedence 5 times, namely in QS al-Maidah verse 76, Surah Yunus verse 49, QS Thaha verse 89, Surah al-Furqan verse 3, and QS al-Fath verse 11. The precedence of naf'an is because the main benefits and precedence of dharran are because the verse relates to torture.